2020
DOI: 10.1038/s41415-020-1424-y
|View full text |Cite
|
Sign up to set email alerts
|

Oral manifestations of vitamin D deficiency in children

Abstract: Oral manifestations of vitamin D deficiency in children In this paper, we highlight the importance of Vitamin D to the development of the permanent dentition,and discuss management options of cases with chronological enamel hypoplasia due to nutritional vitamin D deficiency. Vitamin D-An overview Vitamin D, along with Parathyroid hormone (PTH), fibroblast growth hormone 23 (FGF23), and calcitonin, are regulators of the calcium and phosphate metabolic pathways, which are key to the development and maintenance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Although the underlying mechanisms are not clear, disturbances in calcium homeostasis and vitamin D deficiencies that can occur in NS 2 , in particular during dental development, have been associated with the development of EH 6 . A correlation between an early age of onset of the NS and the prevalence of CEH has been reported 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the underlying mechanisms are not clear, disturbances in calcium homeostasis and vitamin D deficiencies that can occur in NS 2 , in particular during dental development, have been associated with the development of EH 6 . A correlation between an early age of onset of the NS and the prevalence of CEH has been reported 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Chronological enamel hypoplasia (CEH) is a developmental defect that presents with distinct characteristic banding around the crowns of teeth. The location of the defective enamel is a permanent chronological record of past disturbances, corresponding with the age of disease onset 6 . Enamel hypoplasia (EH) is a well-known phenomenon in children with chronic renal failure (CRF) 7 .…”
mentioning
confidence: 99%
“…This allows a mapping chronological timeframe (Figure 2) and a classification by putative biological mechanisms (Figure 3). Some factors are well-reported and have been the subject of review papers (not analyzed in this SC): severe respiratory distress syndromes (146), preterm birth (147), vitamin D deficiencies during childhood (148), cleft palate (149), syphilis (150), excess fluoride (151), renal disorders (133), diabetes type 1 (152), cancer therapy (153), organic pollutants (154), dioxin exposure (155), dietary components (156), drugs during pregnancy and the first year of life (157), and drugs during infancy (158); these do not always relay clear evidence between DDE and risk factors supporting our hypothesis of accumulation and synergy effects. Generalist reviews were found, but either did not identify as many factors in a systematic way (159), or focused on one type of DDE (160), dentition (161) or treatment (162).…”
Section: Highlight the Current Literature And Better Understand The N...mentioning
confidence: 99%
“…Including the process of tooth development known as odontogenesis [3] . Adequate levels are considered above 50 nmol/L, with deficiency defined as below 25 nmol/L [4] .…”
Section: Introductionmentioning
confidence: 99%
“…In children, the deficiency can lead to rickets, a condition marked by poor bone mineralization, while adults may experience osteomalacia. Additionally, maternal Vitamin D levels are crucial for prenatal health, influencing the risk of several conditions including gestational diabetes and low birth weight [4] .…”
Section: Introductionmentioning
confidence: 99%